Sterically Demanding Unsymmetrical Diaryl-λ(3)-iodanes for Electrophilic Pentafluorophenylation and an Approach to α-Pentafluorophenyl Carbonyl Compounds with an All-Carbon Stereocenter - Matsuzaki, Kohei (ChemistryOpen, 2014)
A sterically demanding unsymmetrical pentafluorophenyl-triisopropylphenyl-λ(3)-iodane was developed as an effective reagent for the electrophilic pentafluorophenylation of various β-keto esters and a β-keto amide. 17 examples of α-pentafluorophenylated 1,3-dicarbonyl compounds 3 having a quaternary carbon center are provided. The resulting compounds were nicely transformed into chiral α-pentafluorophenyl ketones with an all-carbon stereogenic center in high yields and high enantioselectivities using asymmetric organocatalysis (up to 98 % ee) or asymmetric metal catalysis (up to 82 % ee).